2023
DOI: 10.1038/s41419-023-06099-y
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP3 promotes the progression of colorectal cancer and mediates cetuximab resistance by stabilizing EGFR mRNA in an m6A-dependent manner

Li-Jie Chen,
Hui-Ye Liu,
Zhi-Yuan Xiao
et al.

Abstract: Insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3), an RNA-binding protein, is associated with tumorigenesis and progression. However, the exact molecular mechanisms of IGF2BP3 in colorectal cancer (CRC) oncogenesis, progression, and drug resistance remain unclear. This study found that IGF2BP3 was upregulated in CRC tissues. Clinically, the elevated IGF2BP3 level is predictive of a poor prognosis. Functionally, IGF2BP3 enhances CRC tumorigenesis and progression both in vitro and in vivo. Mechanisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Previous studies have provided evidence that EGFR was required for the regenerative proliferation of auditory supporting cells in mammals and birds [50], and impaired glycolysis promotes alcohol exposure-induced apoptosis in HEI-OC1 cells by inhibiting EGFR signalling [51]. Interestingly, recent research has found that reader proteins IGF2BP3 or YTHDF2 also can directly bind to the m6A modification site of EGFR mRNA to change its stability [52,53]. However, the m6 A modification of EGFR mRNA in ARHL is still poorly understood and its role in ARHL is the next step in our research plan.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided evidence that EGFR was required for the regenerative proliferation of auditory supporting cells in mammals and birds [50], and impaired glycolysis promotes alcohol exposure-induced apoptosis in HEI-OC1 cells by inhibiting EGFR signalling [51]. Interestingly, recent research has found that reader proteins IGF2BP3 or YTHDF2 also can directly bind to the m6A modification site of EGFR mRNA to change its stability [52,53]. However, the m6 A modification of EGFR mRNA in ARHL is still poorly understood and its role in ARHL is the next step in our research plan.…”
Section: Discussionmentioning
confidence: 99%
“…World J Oncol. 2024;15 (1):100-113 ing to N6-methyladenosine-modified target mRNAs [1]. Meanwhile, IGF2BPs were shown to regulate the mRNA stability and modulate neural stem cell proliferation [6].…”
Section: Dai Et Almentioning
confidence: 99%
“…The RNA-binding protein, IGF2BP3, plays a role in the regulation of mRNA stability during carcinogenesis [ 1 ]. There is, however, little information about their paralogue-specific functions in tumor cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations